WHO ARE THE KEY PLAYERS IN ENERGY POLICY IN POLAND? THE ROLE OF INTEREST GROUPS IN ENERGY TRANSITION - Urszula KURCZEWSKA (Eastern European Journal of Regional Studies, 2023)
The paper presents an analysis of the role of interest groups in Poland's energy policy in the context of the EU climate and energy policy. The main aim of the analysis is to try to answer the question of who shapes the Polish energy policy, which stakeholders have the greatest impact on, who are the key players, and what kind of interest intermediation system has developed in the energy sector. Poland's energy mix is dominated by coal, which results from the ownership structure in the energy sector, strong influence of conventional (coal) energy companies and centralization of energy policy. The interests of coal energy companies are protected by the government both in Poland and at the EU level. The research puts forward a thesis that Polish energy policy is co-shaped by conventional energy companies, which leads to their monopolistic position and the formation of a neocorporatist model with elements of statism, and the process of illiberal backlash and creeping authoritarianism further strengthens their role. Privileging the interests of the state-owned energy companies hampers the process of energy transition in Poland, which is contrary to the EU's climate and energy policy.